Curing treatment process for bone china color-baking composite coloring glaze surface

By combining biomimetic micro-pit etching and silk protein activating liquid spraying with multi-temperature gradient heating treatment, the problem of insufficient anchoring in the bone china color firing process is solved, achieving firm adhesion and color uniformity of the composite glaze, and meeting the durability and wear resistance requirements of high-end bone china products.

CN121135484APending Publication Date: 2025-12-16SHANGHAI HANSHAN PORCELAIN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511109615.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

In existing bone china coloring and firing processes, the pretreatment stage often uses a single mechanical grinding or chemical cleaning method, which makes it difficult to build a deep anchoring structure on the surface of the body. This leads to insufficient anchoring and interlayer separation under high-temperature sintering or thermal shock, and it is also difficult to achieve a stable bond of multi-layer coloring structures.

Method used

The substrate is formed by biomimetic micro-pit etching and silk protein activation liquid spraying. Combined with composite coloring and multi-temperature gradient heating treatment, the honeycomb structure provides physical anchoring points and chemical adsorption capacity, which enhances the adhesion strength of the composite glaze. Furthermore, the color uniformity and optical performance are improved by using nano-pigments and metal oxide films.

Benefits of technology

It significantly improves the adhesion strength and color uniformity of the composite glaze, has good antibacterial properties and wear resistance, and ensures that the glaze does not easily separate during high-temperature sintering, meeting the quality standards for collectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121135484A_ABST
    Figure CN121135484A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, and discloses a bone china color baking composite coloring glaze surface curing treatment process, which comprises the following steps: S1, pretreating a bone china biscuit, including bionic micro-pit etching and silk protein activating solution spraying, to form a substrate with preset adhesiveness; s2, glaze is prepared, composite coloring is conducted on the surface of the substrate, and a coloring layer comprising a bottom-layer coloring structure and a surface-layer coloring structure is formed; and S3, carrying out curing treatment on the bone china biscuit with the coloring layer, so that the coloring layer and the bone china biscuit are combined to form a composite glaze surface. A honeycomb structure formed by bionic micro-pit etching provides a physical anchoring site for a substrate, and meanwhile, active ingredients in the fibroin activating solution and the volcanic ash powder synergistically enhance the chemical adsorption capacity, so that the dual effects of mechanical riveting and chemical bonding are generated between a glaze layer and a bone china green body, and the adhesion strength of a composite glaze surface is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of ceramic materials, in particular to a bone porcelain color roasting composite coloring glaze surface solidification treatment process. BACKGROUND

[0002] High-end bone porcelain products continuously pursue the synchronous improvement of rich expression of glaze color and physical durability in the field of artistic decoration. The market demand for products with complex pattern accurate reproduction ability and long-term use anti-wear characteristics is increasing, and consumers' attention to environmentally friendly materials and energy-saving manufacturing processes is also increasing, which promotes the development of bone porcelain color roasting technology towards composite functionalization. It is necessary to innovate the process to realize the stable combination of multi-level coloring structure within a single sintering framework, and ensure that the glaze surface meets the collection level quality standards in terms of mechanical properties and chemical stability.

[0003] In the existing bone porcelain color roasting process, the pretreatment link often uses single mechanical polishing or chemical cleaning method, which can only form a superficial rough surface or rely on temporary physical adsorption, and it is difficult to build a deep anchoring structure on the surface of the body. Under high temperature sintering or thermal shock, it is easy to cause interlayer separation due to insufficient anchoring. SUMMARY

[0004] In view of the defects of the prior art, the present application provides a bone porcelain color roasting composite coloring glaze surface solidification treatment process, which solves the problem that the pretreatment link of the prior art often uses single mechanical polishing or chemical cleaning method, which can only form a superficial rough surface or rely on temporary physical adsorption, and it is difficult to build a deep anchoring structure on the surface of the body. Under high temperature sintering or thermal shock, it is easy to cause interlayer separation due to insufficient anchoring.

[0005] To achieve the above purpose, the present application is realized by the following technical scheme: a bone porcelain color roasting composite coloring glaze surface solidification treatment process, comprising the following steps:

[0006] S1, pretreating the bone porcelain blank, the pretreatment including biomimetic micro-pit etching and silk fibroin activation liquid spraying, forming a substrate with a preset adhesion;

[0007] S2, preparing glaze and implementing composite coloring on the surface of the substrate, forming a coloring layer containing a bottom coloring structure and a surface coloring structure;

[0008] S3, solidifying the bone porcelain blank with the coloring layer to form a composite glaze surface.

[0009] By adopting the above technical scheme, the honeycomb structure formed by biomimetic micro-pit etching provides physical anchoring points for the substrate, and the active ingredients in the silk fibroin activation liquid and the volcanic ash powder synergistically enhance the chemical adsorption capacity, significantly improving the adhesion strength of the composite glaze surface.

[0010] Preferably, the biomimetic micro-pit etching in S1 is to polish the surface of the blank with a mixture of fine quartz sand and white vinegar paste in a circular motion, the fine quartz sand is 200 mesh, the ratio of fine quartz sand to white vinegar in the mixed paste is 3:1, the polishing time is 25-35 seconds, and the formed honeycomb micro-pits have a depth of 5-10 μm.

[0011] By adopting the above technical scheme, the biomimetic micro-pit etching polishes the surface of the blank with a mixture of fine quartz sand and white vinegar paste in a circular motion to form honeycomb micro-pits. These micro-pits can increase the roughness of the surface of the blank, provide more physical anchoring space for the subsequent spraying of the silk protein activation solution and the adhesion of the colored layer, enable the subsequent coating to be more closely embedded in the micro-pits, enhance the bonding strength of the substrate and each subsequent layer, and provide a physical basis for the firm adhesion of the composite glaze.

[0012] Preferably, the spraying of the silk protein activation solution in S1 is to dissolve silk protein in a citric acid solution, add volcanic ash powder to prepare an active coating solution, and uniformly spray the solution on the surface of the micro-pits with a spray bottle. The coating is dried with hot air at 55-65°C for 1.5-2.5 minutes. The concentration of the citric acid solution is 5%, and the addition amount of the volcanic ash powder is 5%. The volcanic ash powder is sieved through a 300 mesh sieve.

[0013] By adopting the above technical scheme, the spraying of the silk protein activation solution is to dissolve silk protein in a citric acid solution, add volcanic ash powder to prepare a coating solution, and uniformly spray the solution on the surface of the micro-pits. The coating is dried with hot air, which enhances the activity of the silk protein under the action of the citric acid and increases the active sites and roughness of the coating surface. The active surface layer formed after drying can be closely combined with the micro-pit structure, providing chemical adsorption capacity and physical anchoring basis for the subsequent colored layer.

[0014] Preferably, the composite coloring in S2 comprises the following steps in sequence:

[0015] S201, bottom layer coloring, mixing nano pigments and glaze to form a colored slurry to be applied to the surface of the substrate by spraying;

[0016] S202, surface layer coloring, depositing a metal oxide film on the surface of the bottom layer coloring layer, and then applying an overglaze color layer by transfer printing.

[0017] By adopting the above technical scheme, the bottom layer coloring in S201 mixes nano pigments and glaze to form a colored slurry, which is uniformly applied to the surface of the substrate by spraying. The colored slurry forms a uniform bottom layer coloring base on the surface of the substrate with the help of spraying. The surface layer coloring in S202 deposits a metal oxide film on the surface of the bottom layer coloring layer, which enhances the structural strength and optical performance of the surface layer by utilizing the physical properties of the film. Then, an overglaze color layer is applied by transfer printing, which ensures the clarity and adhesion stability of the overglaze color pattern.

[0018] Preferably, in S201, the mass ratio of the nano-colorant to the glaze in the colored slurry is 1-10:100, and the nano-colorant is a rare earth doped colorant, and the mass fraction of the rare earth element in the colorant is 1-5:100;

[0019] By adopting the above technical solution, the doping of the rare earth element can improve the dispersion stability of the nano-colorant and avoid particle agglomeration. The appropriate mixing ratio can ensure that the colorant is uniformly distributed in the glaze, neither unevenly dispersed due to too high a proportion nor affecting the coloring effect due to too low a proportion. The spraying method can make the colored slurry uniformly cover the surface of the substrate, and the color enhancement effect brought by the rare earth doping can finally form a bottom coloring structure with uniform color and stable color development, providing a good foundation for surface coloring.

[0020] In S202, the metal oxide film is a composite layer of titanium dioxide and iron oxide, and the film thickness is 50-200 nm. The overglaze color contains a low-melting-point glass phase, and the softening point temperature of the low-melting-point glass phase is 500-650℃.

[0021] By adopting the above technical solution, the titanium dioxide and iron oxide composite film on the surface of the bottom coloring layer enhances the hardness and wear resistance of the surface layer through the synergistic effect of the two oxides, and at the same time, the light reflection and absorption characteristics enrich the color level and saturation. The low-melting-point glass phase contained in the overglaze color will soften and melt during the solidification process, promoting the close combination of the overglaze color layer and the bottom coloring layer. The transfer printing method ensures the clarity and adhesion stability of the overglaze color pattern.

[0022] Preferably, the glaze prepared in S2 includes a base glass phase, a fluxing adjustment phase, a functional phase, and a suspending agent.

[0023] The base glass phase includes potassium feldspar, quartz, kaolin, and spodumene.

[0024] The fluxing adjustment phase includes zinc oxide and borax.

[0025] The functional phase includes nano-zinc oxide and nano-zirconium dioxide.

[0026] The suspending agent includes sodium carboxymethyl cellulose and sodium alginate.

[0027] By adopting the above technical solution, the components of the base glass phase synergistically form a stable glass network structure to provide a solid framework for the glaze surface. The fluxing adjustment phase effectively reduces the melting temperature of the glaze, promoting its uniform flow and full filling of the substrate micro-pits during the solidification process, and enhancing the bonding force with the body. The functional phase enhances the wear resistance and antibacterial performance of the glaze surface. The suspending agent maintains the dispersion stability of the glaze slurry and prevents particle sedimentation.

[0028] Preferably, the amount of the glaze is:

[0029] Potassium feldspar 20-30 parts by weight, quartz 15-20 parts by weight, kaolin 10-15 parts by weight, spodumene 8-12 parts by weight, zinc oxide 5-10 parts by weight, borax 3-7 parts by weight, nano zirconium dioxide 2-4 parts by weight, nano zinc oxide 3-7 parts by weight, sodium carboxymethyl cellulose 0.2-0.4 parts by weight, sodium alginate 0.4-0.6 parts by weight.

[0030] By adopting the above technical solutions: potassium feldspar, quartz, kaolin, and spodumene are used as the basic glass phases. When mixed in this range, a stable glass network structure can be formed, providing a basic framework for the glaze. Zinc oxide and borax are used as fluxing and regulating phases. When mixed in this range, the melting temperature of the glaze can be effectively reduced, promoting uniform flow of the glaze during the curing process and filling the micro-pits in the substrate. Nano-zirconia and nano-zinc oxide are used as functional phases. When mixed in this amount, the wear resistance and antibacterial properties of the glaze can be enhanced. Sodium carboxymethyl cellulose and sodium alginate are used as suspending agents. When mixed in this ratio, the dispersion stability of the glaze slurry can be maintained, preventing particle sedimentation.

[0031] Preferably, the preparation of the glaze includes:

[0032] Raw material pretreatment, mixing and ball milling, preparation of suspension system and static curing;

[0033] The ratio of material, balls, and water in the ball mill is 1:2:0.8, the ball mill speed is 250-350 r / min, and the time is 3-5 hours.

[0034] The static curing process is carried out at 25±2℃ and 50-60% relative humidity for 40-50 hours.

[0035] By adopting the above technical solution: first, the raw materials are pretreated to meet the processing requirements, then balls and water are added in proportion for ball milling. Through grinding at a certain speed and time, the raw material particles are fully refined and uniformly mixed, reducing particle agglomeration. Subsequently, a suspension system containing a suspending agent is prepared to maintain the dispersion stability of the slurry and prevent particle sedimentation. Finally, the slurry is left to stand and mature in a suitable temperature and humidity environment, allowing the internal stress of the slurry to be released slowly, promoting further interaction and uniform distribution among the components. This results in a glaze with a delicate texture, uniform dispersion, and good stability, laying the foundation for uniform application and good bonding with the substrate during subsequent composite coloring.

[0036] Preferably, the curing process in S3 employs multi-temperature gradient heating, including:

[0037] Low temperature range: 200-400℃, keep warm for 20-30 minutes;

[0038] Medium temperature range: 400-650℃, keep warm for 30-40 minutes;

[0039] High temperature range: 750-800℃, keep warm for 20-40 minutes.

[0040] By adopting the above technical solutions: the low-temperature stage can fully remove moisture and volatile substances from the coloring layer and glaze, avoiding bubbles or pinholes caused by the volatilization of impurities during subsequent high-temperature treatment; the medium-temperature stage can promote the gradual softening of low-melting-point components in the glaze and form a uniform melting base, while slowly releasing the thermal stress accumulated in the early stage, reducing structural deformation caused by drastic temperature changes; and the high-temperature stage allows the glaze to completely melt and fully impregnate and fuse with the bone china body and coloring layer, strengthening the physical and chemical bonding between the layers.

[0041] Preferably, the curing process employs a gradient cooling method, with the cooling rate gradually decreasing from 10°C / minute to 2°C / minute.

[0042] By adopting the above technical solutions, the gradient cooling scheme gradually slows down the cooling rate from a relatively fast rate to a slower rate, allowing the glaze layer and the bone china body to adapt to temperature changes synchronously during the cooling process. This slowly releases the internal stress caused by thermal expansion and contraction, avoiding excessive stress concentration due to the difference in thermal expansion characteristics caused by sudden changes in the cooling rate. This prevents defects such as cracks in the glaze surface and ensures a tight bond between the composite glaze and the body.

[0043] This invention provides a curing process for a composite coloring glaze on bone china. It offers the following advantages:

[0044] 1. This invention provides physical anchoring points for the substrate by forming a honeycomb structure through biomimetic micro-pit etching. At the same time, the active ingredients in the silk protein activating liquid and the volcanic ash powder synergistically enhance the chemical adsorption capacity, so that the glaze layer and the bone china body produce a dual effect of mechanical riveting and chemical bonding, thereby improving the adhesion strength of the composite glaze surface.

[0045] 2. The nano zinc oxide added to the glaze of the present invention releases zinc ions and generates active oxygen during the curing process, which destroys the cell membrane structure of microorganisms and interferes with their metabolic process. At the same time, the lanthanide elements in the rare earth doped pigment catalyze the oxidation reaction, and the synergistic effect gives the glaze a lasting antibacterial property.

[0046] 3. This invention uses multi-temperature gradient heating. In the low-temperature zone, volatile substances are fully eliminated to avoid the formation of bubbles. In the medium-temperature zone, low-melting-point components are uniformly melted and thermal stress is released. In the high-temperature zone, the glaze is completely vitrified and deeply bonded to the body. The gradient cooling simultaneously adjusts the shrinkage rate of the glaze and the body, reduces the phenomenon of interface stress concentration, and ensures the integrity of the glaze surface.

[0047] 4. In this invention, nano-pigments are uniformly dispersed in the glaze matrix under a limited ratio in composite coloring. The upconversion luminescence effect of the rare earth elements in the bottom layer enhances the color saturation. The surface titanium dioxide and iron oxide composite film regulates the color level through the light interference effect. After the low melting point glass phase melts, it fills the gaps between molecules, and together they form a full and uniform visual effect. Attached Figure Description

[0048] Figure 1 This is a flow chart of a bone china coloring and curing process for composite coloring glaze. Detailed Implementation

[0049] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0050] Please see the appendix Figure 1 This invention provides a bone china coloring and curing process for composite coloring glaze, comprising the following steps:

[0051] S1. Pre-treatment of bone china blanks, including biomimetic micro-pit etching and spraying of silk protein activating liquid to form a substrate with pre-defined adhesion.

[0052] S2. Prepare the glaze and perform composite coloring on the substrate surface to form a coloring layer containing a bottom coloring structure and a surface coloring structure;

[0053] S3. The bone china blank with the coloring layer is cured to combine the coloring layer with the bone china blank to form a composite glaze.

[0054] In S1, the biomimetic micro-pit etching is performed by grinding the surface of the blank with a mixture of fine quartz sand and white vinegar in a circular motion. The fine quartz sand is 200 mesh, and the ratio of fine quartz sand to white vinegar in the mixture is 3:1. The grinding time is 25-35 seconds, and the depth of the honeycomb-shaped micro-pits formed is 5-10μm.

[0055] The silk protein activating solution spraying in S1 involves dissolving silk protein in citric acid solution, adding volcanic ash powder to make an active coating solution, and then spraying it evenly onto the surface of the micro-pits with a spray bottle. It is then dried with hot air at 55-65℃ for 1.5-2.5 minutes. The concentration of the citric acid solution is 5%, the amount of volcanic ash powder added is 5%, and the volcanic ash powder is passed through a 300-mesh sieve.

[0056] Specifically, a paste is made by mixing 200-mesh fine quartz sand and white vinegar in a 3:1 ratio. This paste is then polished on the surface of the unglazed blank in a circular motion for 25-35 seconds to form honeycomb-like micro-pits of 5-10 μm. The silk protein activation liquid is then sprayed onto the surface of the micro-pits by dissolving silk protein in a 5% citric acid solution and adding 5% volcanic ash powder that has passed through a 300-mesh sieve. After being evenly sprayed onto the surface of the micro-pits, the mixture is dried with hot air at 55-65℃ for 1.5-2.5 minutes. The honeycomb-like micro-pits provide physical anchoring points by increasing the surface roughness of the unglazed blank. The silk protein in the silk protein activation liquid interacts with citric acid to enhance chemical activity, while the volcanic ash powder further improves the surface activity and roughness of the coating. After drying, the coating and the micro-pit structure are tightly bonded together, synergistically enhancing the physical adsorption and chemical bonding force between the subsequent coloring layer and the substrate, laying the foundation for the firm adhesion of the composite glaze.

[0057] The composite coloring in S2 includes, in sequence:

[0058] S201, Underlying coloring: Nano pigments are mixed with glaze to form a coloring paste, which is then applied to the substrate surface by inkjet printing.

[0059] S202, Surface coloring: A thin film of metal oxide is deposited on the surface of the bottom coloring layer, and then an overglaze coloring layer is applied by transfer printing.

[0060] In S201, the mass ratio of nano-pigment to glaze in the coloring paste is 1-10:100. The nano-pigment is a rare earth-doped pigment, and the mass percentage of rare earth elements in the pigment is 1-5:100.

[0061] In S202, the metal oxide film is a composite layer of titanium dioxide and iron oxide with a thickness of 50-200 nm. The overglaze color contains a low-melting-point glass phase with a softening temperature of 500-650℃.

[0062] Specifically, in S2, the composite coloring process first involves bottom layer coloring via S201, where rare earth-doped nano-pigments and glazes are mixed at a mass ratio of 1-10:100 to form a coloring slurry, which is then applied to the substrate surface via inkjet printing. Next, surface coloring is performed via S202, where a titanium dioxide and iron oxide composite film with a thickness of 50-200 nm is deposited on the surface of the bottom coloring layer. Subsequently, an overglaze coloring layer containing a low-melting-point glass phase with a softening point temperature of 500-650℃ is applied via transfer printing. The specific proportion of nano-pigments mixed with the glazes in the bottom coloring process, combined with rare earth doping, enhances the dispersion and color stability of the pigments. The inkjet printing method ensures uniform coloring, and the surface metal oxide composite film improves surface hardness and wear resistance. At the same time, the synergistic effect of titanium dioxide and iron oxide enhances light reflection and color gradation. The low-melting-point glass phase melts during the curing process, promoting a tight bond between the surface and the bottom layers.

[0063] The glaze prepared in S2 includes a basic glass phase, a fluxing and conditioning phase, a functional phase, and a suspending agent;

[0064] The basic glassy phase includes potassium feldspar, quartz, kaolin, and spodumene;

[0065] The fluxing conditioning phase includes zinc oxide and borax;

[0066] The functional phases include nano zinc oxide and nano zirconium dioxide;

[0067] The suspending agent contains sodium carboxymethyl cellulose and sodium alginate.

[0068] The amount of glaze used is:

[0069] Potassium feldspar 20-30 parts by weight, quartz 15-20 parts by weight, kaolin 10-15 parts by weight, spodumene 8-12 parts by weight, zinc oxide 5-10 parts by weight, borax 3-7 parts by weight, nano zirconium dioxide 2-4 parts by weight, nano zinc oxide 3-7 parts by weight, sodium carboxymethyl cellulose 0.2-0.4 parts by weight, sodium alginate 0.4-0.6 parts by weight.

[0070] Specifically, potassium feldspar, quartz, kaolin, and spodumene serve as the basic glass phases. When mixed in this range, they can form a stable glass network structure, providing a basic framework for the glaze. Zinc oxide and borax serve as fluxing and regulating phases, effectively reducing the melting temperature of the glaze, promoting uniform flow of the glaze during curing, and filling the micro-pits in the substrate. Nano-zirconia and nano-zinc oxide serve as functional phases, which, at this dosage, can enhance the wear resistance and antibacterial properties of the glaze. Sodium carboxymethyl cellulose and sodium alginate serve as suspending agents, which, at this ratio, can maintain the dispersion stability of the glaze slurry and prevent particle sedimentation. The synergistic effect of the components, when mixed in the above dosages, gives the glaze good formability, bonding strength, and functional properties.

[0071] The preparation of glaze includes:

[0072] Raw material pretreatment, mixing and ball milling, preparation of suspension system and static curing;

[0073] The ratio of material, balls, and water in the ball mill is 1:2:0.8. The ball mill speed is 250-350 r / min, and the time is 3-5 hours.

[0074] The aging process is carried out at 25±2℃ and 50-60% relative humidity for 40-50 hours.

[0075] Specifically, the ball milling process, through a specific ratio of material to water, rotation speed, and duration, utilizes the mechanical grinding and impact of the ball milling media to fully refine the raw material particles and achieve uniform mixing, reducing particle agglomeration. The preparation of the suspension system maintains the dispersion stability of the slurry and prevents particle sedimentation. The static curing process, under suitable temperature and humidity conditions, allows sufficient time for the internal stress of the slurry to be slowly released, promoting further mutual penetration and interaction between the components. This results in a finer glaze texture and a more uniform component distribution, ensuring uniformity and adhesion when subsequently mixed with colorants and applied to the substrate.

[0076] The curing process in S3 employs multi-temperature gradient heating, including:

[0077] Low temperature range: 200-400℃, keep warm for 20-30 minutes;

[0078] Medium temperature range: 400-650℃, keep warm for 30-40 minutes;

[0079] High temperature range: 750-800℃, keep warm for 20-40 minutes.

[0080] Specifically, the multi-temperature gradient heating of the curing process is achieved by sequentially controlling three temperature ranges. First, the temperature is maintained at a low temperature range of 200-400℃ for 20-30 minutes to remove moisture and volatile impurities from the coloring layer and glaze, preventing bubbles or cracks caused by impurity volatilization at subsequent high temperatures. Then, the temperature is maintained at a medium temperature range of 400-650℃ for 30-40 minutes to allow the low-melting-point components in the glaze to soften initially and form a uniform molten base, while gradually releasing the thermal stress accumulated in the early stage and reducing the risk of structural deformation. Finally, the temperature is maintained at a high temperature range of 750-800℃ for 20-40 minutes to allow the glaze to completely melt and fully impregnate and bond with the bone china body and coloring layer.

[0081] The curing process employs a gradient cooling method, with the cooling rate gradually decreasing from 10℃ / minute to 2℃ / minute.

[0082] Specifically, the gradient cooling process for curing involves initially cooling at a rate of 10°C / minute after the high-temperature stage, then gradually slowing the cooling rate down to a final rate of 2°C / minute. This allows the glaze layer and the bone china body to slowly release internal stress during temperature changes, preventing excessive stress caused by the difference in thermal expansion coefficients due to rapid cooling, which could lead to cracks. This ensures the structural integrity of the composite glaze and its bonding stability with the body, maintaining a good morphology and bonding state during cooling. The following examples and comparative examples further illustrate this application in detail.

[0083] Specific types of raw materials:

[0084] The silk protein was purchased from Jiangsu Xinyuan Silk Cocoon, brand name SY-01;

[0085] Citric acid was purchased from Shandong Yingxuan Industry Co., Ltd., and is food grade.

[0086] The volcanic ash powder was purchased from the Lingshou County Mineral Products Processing Plant and screened through a 300-mesh sieve.

[0087] Potassium feldspar was purchased from Hengcheng Mineral Products, Lingshou County, grade K-25;

[0088] The quartz was purchased from Donghai County Silicon Micro Powder Factory, grade Q-18;

[0089] The kaolin was purchased from Yangshan Mine in Suzhou, grade G-12;

[0090] The spodumene was purchased from Yichun Mining in Jiangxi Province, grade L-10.

[0091] Zinc oxide was purchased from Liuzhou Zinc Products Co., Ltd., grade ZnO-8;

[0092] The borax was purchased from Tianjin Borax Factory; it is industrial grade.

[0093] The nano-zirconia was purchased from Shanghai Aladdin Biochemical, grade ZrO2-NP3;

[0094] The nano zinc oxide was purchased from Nanjing Xianfeng Nano, grade ZnO-NP5;

[0095] Sodium carboxymethyl cellulose was purchased from Shandong Heda Co., Ltd., brand name CMC-Na-HV; sodium alginate was purchased from Qingdao Mingyue Seaweed Co., Ltd., brand name SA-05.

[0096] Zirconia spheres were purchased from Zibo Yubang Ceramics, with a diameter of 5mm;

[0097] The nano pigments are purchased from Yixing Pigment Factory, with rare earth content of 1-5%.

[0098] Titanium dioxide was purchased from Panzhihua Iron and Steel Group Titanium Industry, grade PT-100;

[0099] The iron oxide was purchased from Shanghai Pigment Factory, grade Fe2O3-02;

[0100] The low-melting-point glass phase was purchased from Schott in Germany, grade SG-600.

[0101] Preparation Example 1:

[0102] Preparation of silk fibroin activating solution

[0103] Dissolve silk fibroin in a 5% citric acid solution, add volcanic ash powder that has passed through a 300-mesh sieve at a ratio of 5%, and stir for 20 minutes until completely mixed to obtain an activated silk fibroin solution.

[0104] Preparation Example 2:

[0105] Glaze preparation

[0106] Weigh out 25 parts by weight of potassium feldspar, 18 parts by weight of quartz, 12 parts by weight of kaolin, 10 parts by weight of spodumene, 8 parts by weight of zinc oxide, 5 parts by weight of borax, 3 parts by weight of nano-zirconia, and 5 parts by weight of nano-zirconia. Crush them to 200 mesh and add them to a ball mill. Add zirconia balls and deionized water at a material-ball-water ratio of 1:2:0.8 and ball mill at 300 r / min for 4 hours. Separately, dissolve 0.3 parts by weight of sodium carboxymethyl cellulose and 0.5 parts by weight of sodium alginate in 13.2 parts by weight of deionized water and stir until completely dissolved. Mix the ball-milled slurry with the suspension, stir for 30 minutes, seal and let stand for 48 hours to mature, and obtain the glaze.

[0107] Example:

[0108] Example 1

[0109] S1. Pre-treatment of the bone china blank: First, biomimetic micro-pit etching is used. A paste is made by mixing 200-mesh fine quartz sand and white vinegar in a 3:1 ratio. The paste is then polished on the surface of the blank in a circular motion for 30 seconds to form 8μm honeycomb-like micro-pits. Next, silk protein activating liquid is sprayed on and dried with hot air at 60℃ for 2 minutes to obtain the base.

[0110] S2, Prepare the glaze and implement composite coloring on the substrate surface. First, mix the nano-coloring material with the glaze at a mass ratio of 3% and the rare earth nano-coloring material to form a slurry. Apply the slurry to the bottom layer by spraying. Then, deposit an 80nm titanium dioxide and iron oxide composite film and transfer the glaze color containing a low melting point glass phase with a softening point of 550℃ to form the coloring layer. S3, Curing treatment is performed on the bone china blank with the coloring layer. The blank is successively heated to 250℃ for 22 minutes, 500℃ for 32 minutes, and 760℃ for 25 minutes. The cooling rate is gradually reduced from 10℃ / minute to 2℃ / minute to form a composite glaze surface.

[0111] Example 2

[0112] S1. Pre-treat the bone china blank by first using biomimetic micro-pit etching. Mix 200-mesh fine quartz sand and white vinegar in a 3:1 ratio to form a paste. Polish the surface of the blank in a circular motion for 30 seconds to form 5μm honeycomb micro-pits. Then spray silk protein activating liquid and dry it with hot air at 58℃ for 1.8 minutes to obtain the base.

[0113] S2. Prepare the glaze and implement composite coloring on the substrate surface. First, mix the nano-coloring material with a rare earth content of 4% and the glaze material at a mass ratio of 7% to form a slurry. Apply the bottom layer by spraying. Then, deposit a 150nm titanium dioxide and iron oxide composite film and transfer the glaze color containing a low melting point glass phase with a softening point of 600℃ to form a coloring layer.

[0114] S3. The bone china blank with the colored layer is cured by sequentially holding it at 350℃ for 28 minutes, 600℃ for 38 minutes, and 790℃ for 35 minutes, with the cooling rate gradually decreasing from 10℃ / minute to 2℃ / minute to form a composite glaze.

[0115] Example 3

[0116] S1. Pre-treat the bone china blank by first using biomimetic micro-pit etching. Mix 200-mesh fine quartz sand and white vinegar in a 3:1 ratio to form a paste. Polish the surface of the blank in a circular motion for 30 seconds to form 10μm honeycomb micro-pits. Then spray silk protein activating liquid and dry it with hot air at 62℃ for 2.2 minutes to obtain the substrate.

[0117] S2. Prepare glaze and implement composite coloring on the substrate surface: First, mix nano-coloring with 3% rare earth nano-coloring at a mass ratio of 5% with glaze to form a slurry, and apply it to the bottom layer by spraying; then deposit a 120nm titanium dioxide and iron oxide composite film, and transfer the glaze color containing a low melting point glass phase with a softening point of 580℃ to form a coloring layer.

[0118] S3. The bone china blank with the colored layer is cured by successively holding it at 300℃ for 25 minutes, 550℃ for 35 minutes, and 780℃ for 30 minutes, with the cooling rate gradually decreasing from 10℃ / minute to 2℃ / minute to form a composite glaze.

[0119] Comparative Example 1

[0120] The difference from Example 3 is that in S1, the biomimetic micro-pit etching is omitted, and the raw blank is cleaned with water and then directly sprayed with silk protein activating liquid. The remaining steps are the same.

[0121] Comparative Example 2

[0122] The difference from Example 3 is that in S1, the surface of the blank is polished with 800-grit sandpaper instead of biomimetic micro-pit etching, while the other pretreatment steps and subsequent processes are the same.

[0123] Comparative Example 3

[0124] The difference from Example 3 is that the glaze does not contain nano zinc oxide and nano zirconium dioxide, but the other glaze components and process steps are the same.

[0125] Comparative Example 4

[0126] The difference from Example 3 is that the S3 curing process is simplified to a single temperature of 800°C for 60 minutes, without the low temperature and medium temperature sections, while the remaining steps are the same.

[0127] Comparative Example 5

[0128] The difference from Example 3 is that the mass ratio of nano-pigment to glaze in S2 is 15%, while the other steps are the same.

[0129] Comparative Example 6

[0130] The difference from Example 3 is that in the preparation of the silk fibroin activation solution, soybean protein is used instead of silk fibroin, while the other preparation steps and process steps are the same.

[0131] Comparative Example 7

[0132] The difference from Example 3 is that the ball milling time for glaze preparation is 2 hours, while the other glaze preparation parameters and process steps are the same.

[0133] Comparative Example 8

[0134] The difference from Example 3 is that the static curing step is omitted in the glaze preparation, and the glaze is directly used for composite coloring after ball milling. The other glaze preparation parameters and process steps are the same.

[0135] Test standards and methods:

[0136] Adhesion strength

[0137] According to Appendix A of GB / T3295-1996 "Test Method for Abrasion Resistance of Ceramic Glaze Surface", the bonding strength between the glaze layer and the body is tested using the tensile method. A 10mm diameter metal clamp is bonded to the center of the glaze surface with epoxy resin, and the cured strength is ≥50MPa. The clamp is then stretched vertically until the glaze layer detaches, and the maximum tensile force is recorded. The strength is calculated using the formula σ=F / A, where F is the maximum tensile force and A is the contact area of ​​the clamp. Five samples are tested in each group, and the average value is taken.

[0138] Color uniformity

[0139] Referring to GB / T3810.16-2016 "Test Methods for Ceramic Tiles - Part 16: Determination of Color Difference", a spectrophotometer (D65 light source, 10° observation angle) was used to measure the Lab value at 10 randomly selected points on the glaze surface, and the color difference ΔE was calculated.

[0140] Rating criteria:

[0141] Level 5: ΔE≤0.5 (no visual color difference);

[0142] Level 4: 0.5 < ΔE ≤ 1.0 (slight color difference);

[0143] Level 3: 1.0 < ΔE ≤ 2.0 (perceptible color difference);

[0144] Level 2: 2.0 < ΔE ≤ 3.0 (obvious color difference);

[0145] Level 1: ΔE > 3.0 (severe color difference);

[0146] Antibacterial rate

[0147] According to GB / T21866-2008 "Determination of Antibacterial Properties of Antibacterial Coatings" and ISO22196-2011, Staphylococcus aureus and Escherichia coli were selected. The bacterial solution (concentration 1×10⁻⁶) was prepared. 5 A drop of CFU / mL was applied to the glazed sample (5cm × 5cm), covered with a sterile membrane, and incubated for 24 hours. The bacterial suspension was then washed off and counted. The antibacterial rate was calculated using the formula: R = (AB) / A × 100%, where A is the average viable count of the control group and B is the average viable count of the sample group. Each group was tested in triplicate.

[0148] Glaze integrity

[0149] According to GB / T3298-2008 "Test Method for Thermal Shock Resistance of Daily-Use Ceramic Ware", the samples were placed in an oven at 220±5℃ for 30 minutes and then rapidly immersed in water at 20℃ for quenching. This cycle was repeated 3 times. The proportion of samples without cracks was counted, with 10 samples in each group.

[0150] abrasion resistance rating

[0151] Referring to GB / T3810.7-2016 "Test Methods for Ceramic Tiles - Part 7: Abrasion Resistance of Glazed Tiles", a sand abrasion tester was used with 0.5mm quartz sand particles and a flow rate of 100g / 10s. The abrasion depth was used for rating.

[0152] Level 5: Depth ≤ 0.1mm (no visible scratches);

[0153] Level 4: 0.1mm < depth ≤ 0.3mm (minor scratch);

[0154] Level 3: 0.3mm < depth ≤ 0.5mm (localized glaze wear);

[0155] Level 2: 0.5mm < depth ≤ 1.0mm (green body exposure < 5%);

[0156] Level 1: Depth > 1.0 mm (bulk exposed ≥ 5%);

[0157] Table 1: Results of Examples and Comparative Examples.

[0158]

[0159]

[0160] Comparison of project explanations:

[0161] The adhesion strength is achieved by the 5-10 μm honeycomb structure formed by biomimetic micro-pit etching, which provides mechanical anchoring points for the glaze layer. The active groups in the silk protein activation solution and the volcanic ash powder synergistically enhance the chemical bonding force. Examples 1-3 achieve 32-35 MPa due to the dual effect. Comparative Example 1, due to the omission of micro-pit etching, suffers from physical anchoring failure, and the strength drops to 15 MPa. Comparative Example 6 uses soybean protein to replace silk protein, but the chemical adsorption capacity is insufficient, and the strength is only 20 MPa.

[0162] Color uniformity: In the bottom layer coloring, rare earth doped nano pigments suppress agglomeration through electrostatic stabilization within a limited mass ratio of 1:10, and the inkjet printing process achieves uniform coverage. In Examples 2-3, the dispersion stability reaches the optimal level 5. In Comparative Example 5, the pigment ratio is increased to 15%, and particle agglomeration causes color difference to exceed the standard, so the rating is reduced to level 2. In Comparative Example 7, the ball milling time is shortened to 2 hours, and insufficient refinement causes color deviation, so the rating is level 3.

[0163] Antibacterial rate: The release of zinc ions from nano zinc oxide destroys the cell membrane of microorganisms. Its photocatalytic active oxygen and rare earth elements undergo a synergistic oxidation reaction. The antibacterial rate of Examples 1-3 exceeds 99%. After removing the functional phases nano zinc oxide and zirconium dioxide from Comparative Example 3, the ion release and catalytic functions are lost, and the antibacterial rate drops to 72%. The antibacterial rates of the other comparative examples are still maintained at >98% because the functional phases are retained.

[0164] The integrity of the glaze surface is ensured through multi-temperature zone gradient curing, which eliminates volatiles, releases thermal stress, and promotes melt wetting in three stages, while gradient cooling achieves synchronous shrinkage of the glaze body. Examples 1-3 achieved an integrity rate of 96%-98%. Comparative Example 4, fired in a single temperature zone at 800℃, experienced violent volatilization and rapid cooling, resulting in bubbles and cracks, with an integrity rate of only 60%. Comparative Example 8, which omitted the glaze curing step, failed to release internal stress, leading to the propagation of microcracks, resulting in an integrity rate of 80%.

[0165] The wear resistance rating is improved by the high hardness and dense structure of the surface composite film. In Example 2, the 150nm thick composite film achieves the optimal rating of 5. In Comparative Example 2, the surface anchoring depth was insufficient, resulting in weakened glaze bonding and a wear resistance rating of 3 due to the use of 800-grit sandpaper to polish instead of micro-pit etching.

[0166] Based on the examples, comparative examples, and table data, it can be seen that the synergistic effect of the biomimetic micro-pit etching and the physical anchoring and chemical adsorption formed by the silk protein activation liquid in the pretreatment stage is the key to improving the adhesion strength. The absence of biomimetic micro-pits or the replacement of protein components will lead to a decrease in adhesion strength of more than 40%. The addition of nano zinc oxide in the glaze directly determines the antibacterial performance. After its absence, the antibacterial rate drops from more than 99% to 72%. In composite coloring, the proportion of nano pigments within the range of 1-10% can ensure color uniformity. Exceeding the limit will cause a sharp drop in grade due to particle agglomeration. The multi-temperature gradient curing and glaze curing process eliminates stress and bubbles in stages, thereby improving the integrity of the glaze surface from 60% to more than 95%.

[0167] Combining Examples 1 to 3 with the data in the table, it can be seen that ball milling time and curing time have a significant impact on product performance. Example 2, which uses 4.5 hours of ball milling and 48 hours of curing, has more uniform glaze particle dispersion, color uniformity of level 5, and abrasion resistance level of level 5, which is better than Example 1, which uses 3.5 hours of ball milling. In contrast, Comparative Example 7, due to the ball milling time being shortened to 2 hours, has color agglomeration, resulting in a drop in color uniformity to level 3, which confirms the effect of ball milling on improving dispersion.

[0168] Furthermore, when the proportion of rare earth elements is in the range of 2%-4%, the antibacterial rate of Example 2 is increased by 0.3% compared with Example 1, suggesting that rare earth and nano zinc oxide have a synergistic catalytic effect. The thickness of the metal oxide film is in the range of 80-150nm. The 150nm film of Example 2 makes the wear resistance level better than the 80nm film of Example 1, indicating that appropriately increasing the film thickness can enhance the surface wear resistance.

[0169] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A process for curing and coloring a composite glaze on bone china, characterized in that, Includes the following steps: S1. Pre-treat the bone china blank, the pre-treatment including biomimetic micro-pit etching and silk protein activating liquid spraying to form a substrate with preset adhesion. S2. Prepare a glaze and perform composite coloring on the surface of the substrate to form a coloring layer containing a bottom coloring structure and a surface coloring structure; S3. The bone china blank with the coloring layer is cured to combine the coloring layer with the bone china blank to form a composite glaze.

2. The bone china coloring and curing process according to claim 1, characterized in that, The biomimetic micro-pit etching in S1 is achieved by grinding the surface of the blank with a mixture of fine quartz sand and white vinegar in a circular motion. The fine quartz sand is 200 mesh, and the ratio of fine quartz sand to white vinegar in the mixture is 3:

1. The grinding time is 25-35 seconds, and the depth of the honeycomb-shaped micro-pits formed is 5-10 μm.

3. The bone china coloring and curing process according to claim 1, characterized in that, The silk protein activating liquid spraying in S1 is prepared by dissolving silk protein in citric acid solution, adding volcanic ash powder to make an active coating liquid, and spraying it evenly on the surface of the micro pits with a spray bottle, and drying it with hot air at 55-65℃ for 1.5-2.5 minutes. The concentration of the citric acid solution is 5%, the amount of volcanic ash powder added is 5%, and the volcanic ash powder is passed through a 300-mesh sieve.

4. The bone china coloring and curing process according to claim 1, characterized in that, The composite coloring in S2 includes, in sequence: S201, Underlying coloring: Nano pigments are mixed with glaze to form a coloring paste, which is then applied to the substrate surface by inkjet printing. S202, Surface coloring: A thin film of metal oxide is deposited on the surface of the bottom coloring layer, and then an overglaze coloring layer is applied by transfer printing.

5. The bone china coloring and curing process according to claim 4, characterized in that, In S201, the mass ratio of nano-pigment to glaze in the coloring paste is 1-10:100, and the nano-pigment is a rare earth-doped pigment, with the mass percentage of rare earth elements in the pigment being 1-5:

100. In S202, the metal oxide film is a composite layer of titanium dioxide and iron oxide with a film thickness of 50-200 nm, and the glaze contains a low-melting-point glass phase with a softening point temperature of 500-650℃.

6. The bone china coloring and curing process according to claim 1, characterized in that, The glaze prepared in S2 includes a basic glass phase, a fluxing and conditioning phase, a functional phase, and a suspending agent. The basic glass phase comprises potassium feldspar, quartz, kaolin, and spodumene; The fluxing conditioning phase includes zinc oxide and borax; The functional phase comprises nano zinc oxide and nano zirconium dioxide; The suspending agent contains sodium carboxymethyl cellulose and sodium alginate.

7. The bone china coloring and curing process according to claim 6, characterized in that, The amount of glaze used is: Potassium feldspar 20-30 parts by weight, quartz 15-20 parts by weight, kaolin 10-15 parts by weight, spodumene 8-12 parts by weight, zinc oxide 5-10 parts by weight, borax 3-7 parts by weight, nano zirconium dioxide 2-4 parts by weight, nano zinc oxide 3-7 parts by weight, sodium carboxymethyl cellulose 0.2-0.4 parts by weight, sodium alginate 0.4-0.6 parts by weight.

8. The bone china coloring and firing composite coloring glaze curing process according to claim 7, characterized in that, The preparation of the glaze includes: Raw material pretreatment, mixing and ball milling, preparation of suspension system and static curing; The ratio of material, balls, and water in the ball mill is 1:2:0.8, the ball mill speed is 250-350 r / min, and the time is 3-5 hours. The static curing process is carried out at 25±2℃ and 50-60% relative humidity for 40-50 hours.

9. The bone china coloring and firing composite coloring glaze curing process according to claim 1, characterized in that, The curing process in S3 employs multi-temperature gradient heating, including: Low temperature range: 200-400℃, keep warm for 20-30 minutes; Medium temperature range: 400-650℃, keep warm for 30-40 minutes; High temperature range: 750-800℃, keep warm for 20-40 minutes.

10. The bone china coloring and firing composite coloring glaze curing process according to claim 9, characterized in that, The curing process employs a gradient cooling method, with the cooling rate gradually decreasing from 10°C / minute to 2°C / minute.